Implementasi Strategi Layanan Prima Pada MAN 2 Kota Serang Sebagai Madrasah Model Berbasis Boarding School - Anis Zohriah; Anis Fauzi; Euis Asyiah; Fazrurrakhman Al Farisi (Mathematics Education Study Program, 2025)
Madrasas as Islamic educational institutions have several advantages compared to other types of schools. The advantages possessed by madrasas include: vitality, fighting power, endurance, adaptability and evolution, and diversity. This research uses a quantitative approach by creating and distributing questionnaires. Primary data was obtained directly from the results of distributing questionnaires to respondents consisting of 100 student representatives, 38 educational staff representatives and 72 teaching staff representatives. Because the data from this research was obtained through distribution of armatures using the Google Form application, the data processing process also uses statistical formula applications that are integrated with existing questionnaires and Google Forms. The research aims to understand the forms of MAN 2 Serang City's excellent service strategy as a madrasa model or as a Boarding School-based madrasa as well as certain factors that support and inhibit the implementation of the excellent service strategy. The results of the research show that Madrasah Aliyah Negeri 2 Serang City acts as a model madrasa based on Islamic boarding schools and is a center for the development of madrasas in the surrounding area. Implementation of quality education services at Madrasah Aliyah Negeri 2 Serang City focuses on providing learning needs, one-stop integrated services (PTSP), digital-based services, as well as facilities and infrastructure services.